The analysis of opportunities of use of heat pumps when carrying out vacuum-evaporating crystallization - G. A. Nosov; D. A. Popov; V. S. Belskaya; V. S. Zhiltsov; D. S. Yakovlev; T. G. Kayralieva (Тонкие химические технологии)
The possibility of using heat pumps of the open and closed type when carrying out vacuumevaporating (adiabatic) crystallization is analysed. The influence of technological parameters on the efficiency of the use of thermal pumps is considered. Thus, areas of change of technological parameters in which it is profitable to use such heat pumps are established. It is shown that the power efficiency of using closed-type heat pumps is higher than that of open-type heat pumps when carrying out adiabatic crystallization.